Selective Knockout of the Vesicular Monoamine Transporter 2 (Vmat2) Gene in Calbindin2/Calretinin-Positive Neurons Results in Profound Changes in Behavior and Response to Drugs of Abuse - König, Niclas; Bimpisidis, Zisis; Dumas, Sylvie; Wallén-Mackenzie, Åsa (Frontiers in Behavioral Neuroscience, 2020)
The vesicular monoamine transporter 2 (VMAT2) has a range of functions in the central nervous system, from sequestering toxins to providing conditions for quantal release of monoaminergic neurotransmitters. Monoamine signaling regulates diverse functions from arousal to mood, movement, and motivation, and dysregulation of VMAT2 function is implicated in various neuropsychiatric diseases. While all monoamine-releasing neurons express the Vmat2 gene, only a subset is positive for the calcium-binding protein Calbindin 2 (Calb2; aka Calretinin, 29 kDa Calbindin). We recently showed that about half of the dopamine neurons in the mouse midbrain are positive for Calb2, and that Calb2 is an early developmental marker of midbrain dopamine cells. Calb2-positive neurons have also been identified in other monoaminergic areas, yet the role of Calb2-positive monoaminergic neurons is poorly understood. To selectively address the impact of Calb2-positive monoaminergic neurons in behavioral regulation, we took advantage of the Cre-LoxP system to create a new conditional knockout (cKO) mouse line in which Vmat2 expression is deleted selectively in Calb2-Cre-positive neurons. In this Vmat2lox/lox;Calb2-Cre cKO mouse line, gene targeting of Vmat2 was observed in several distinct monoaminergic areas. By comparing control and cKO mice in a series of behavioral tests, specific dissimilarities were identified. In particular, cKO mice were smaller than control mice, and showed heightened sensitivity to the stereotypy-inducing effects of amphetamine and slight reductions in preference toward sucrose and ethanol, as well as a blunted response in the elevated plus maze test. These data uncover new knowledge into the role of genetically defined subtypes of neurons in the brain's monoaminergic systems.